2005
DOI: 10.1063/1.1943609
|View full text |Cite
|
Sign up to set email alerts
|

Electron inertia contribution to soliton evolution in an inhomogeneous weakly relativistic two-fluid plasma

Abstract: The contribution of electron inertia to the evolution of solitons in weakly and strongly inhomogeneous plasmas having streaming ions and electrons with weak relativistic effect is studied on the basis of a relevant Korteweg–de Vries equation derived with the help of reductive perturbation technique. Three types of modes (fast, medium, and slow) are found to propagate in the plasma. In case of weak (strong) inhomogeneous plasma, only the fast (slow) mode corresponds to the soliton evolution. For the propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
2
19
1
Order By: Relevance
“…However, the propagation speed of the instabilities is enhanced in both the cases and this effect is linear in nature. Consistent to this observation in an EGRP, other investigators have also found the same effect of relativistic speeds of ions and electrons on the phase velocity of linear ion acoustic waves [16][17][18][19][20][21]31].…”
Section: Numerical Solution To Dispersion Equation and The Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…However, the propagation speed of the instabilities is enhanced in both the cases and this effect is linear in nature. Consistent to this observation in an EGRP, other investigators have also found the same effect of relativistic speeds of ions and electrons on the phase velocity of linear ion acoustic waves [16][17][18][19][20][21]31].…”
Section: Numerical Solution To Dispersion Equation and The Resultssupporting
confidence: 69%
“…Considering a relativistic ion beam and a nonisothermal plasma, Fainshtein and Chernova [15] have investigated high-frequency instabilities and the high power electromagnetic radiation generation from the development of an explosive. Relativistic plasmas have also been explored for the instabilities and nonlinear waves that retain their shapes during propagation [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The width of the structure is given by the expression W L −1 = 2LV L 3 , which means the width is real as long as L is positive. In the present model, we find that L is positive for both the fast and slow modes, contrary to the case of weakly relativistic plasma [26], in which the width is not real for the fast mode.…”
Section: Results and Discussion: Case Of Ionizationcontrasting
confidence: 42%
“…[1][2][3][4][5] However, this equation gets modified with the variable coefficients and/or an additional term that appears due to the presence of density gradient in the case of inhomogeneous plasmas. [6][7][8] On the other hand, relevant KdV equations have been reported in plasma under the effect of external static magnetic field, which show the modification in the soliton propagation characteristics. 3,[9][10][11][12] In ordinary plasma with positive ions and electrons, usually compressive solitons are found to propagate.…”
Section: Introductionmentioning
confidence: 98%